Self-assembly synthesis of petal-like MoS2/Co9S8/carbon nanohybrids for enhanced lithium storage performance - Wu, Bo; Ma, Ran; Liu, Xuewei; Zheng, Yuqi; Guo, Sisheng; Yi, Yanmeng; Sun, Mingtai; Wang, Suhua; Wen, Tao (Frontiers in Energy Research, 2022)
Exploring of advanced anode materials is crucial for the development of the next generation of lithium-ion batteries. Metal sulfides are favored because of their high theoretical capacity and abundant natural resources. However, serious volume changes during charging and discharging pose great challenges to their stability. In this work, petal-like MoS2/Co9S8/C nanohybrids were synthesized via the immobilization of molybdyl acetoacetonate MoO2(acac)2 in ZIF-67 and subsequent combined vulcanization and thermolysis process. Benefiting from the homogeneous bimetallic sulfide and highly conductive carbon layer, the as-obtained MoS2/Co9S8/C nanohybrids exhibited excellent electrochemical performance in terms of rate capability, cycling stability and electrical conductivity. As a result, the MoS2/Co9S8/C anode is found to deliver improved initial discharge capacity of 988.3 mA h g−1 at a current density of 200 mA g−1, and the subsequent cycling durability remains superior capacity retention > 99.9% after 50 cycles, which was roughly 2.25 and 4.17 times larger than that of bare MoS2 and Co9S8/C. Even at a high current density of 1000 mA g−1, the reversible capacity of MoS2/Co9S8/C is still as high as 754.6 mA h g−1, revealing extraordinary rate ability. This work can provide a general approach to design and synthesis other advanced bimetallic chalcogenides for the boosting lithium-ion batteries storage performance.